Pengaruh Sinergi Manajemen Gereja dan Kepemimpinan Transformasional terhadap Efektivitas Multiplikasi Pemimpin dalam Ekosistem Digital - Melki Solon; Yap Hok Gi; Anderson Daniel Sudarto (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Entering the third decade of the 21st century, the church faces the urgency of redefining its existence amidst the shift to a digital ecosystem. This research aims to analyze the synergy between church management and transformational leadership toward the effectiveness of leader multiplication in the Digital 4.0 era. Using a qualitative method with a descriptive-analytical approach through library research, this study explores the integration of modern management theories and theological principles. The findings indicate that church management serves as a vital infrastructure providing operational stability, while transformational leadership acts as a catalyst for innovation and behavioral change in facing VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) conditions. The synergy between these two elements creates a “Digital Shepherding” model, where the digital space is transformed into a theological medium for character formation and spiritual transmission. The study concludes that the effectiveness of leader multiplication is determined by a shift from person-centered leadership to a system-inspired approach that integrates digital capabilities with biblical integrity. Strategic implications suggest that churches must adopt a digital mindset and establish digital leadership laboratories to ensure the sustainability of their mission among Generation Z.